APPLICATION AFFECTION AND SOFTNESS IN LEARNING PROCESS IN KINDERGARTEN - Mayar, Farida (Indonesian Journal of Early Childhood Education Studies, 2013)
Affection and tenderness of affection and tenderness that is indispensable to the realization that conducive learning and fun for children of kindergarten (hereafter TK), thus giving greater possibility in the development of all the potential that a kindergartner. But the reality of love and tenderness are still low by teachers in the learning process i s optimal. Based on the above conclusion can be put forward suggestions to between another kindergarten teacher in order to add insight, knowledge, understanding, and skills to apply the affection and tenderness in the process of learning and training seminars. To institutions such as LPTK advised to give more supplies to teachers and prospective teachers about the techniques of interpersonal relationships special affection and tenderness over the deepening of the psychology of learning materials on kindergarten children.